The role of percutaneous abscess drainage in adult patients with perforated appendicitis - Fatma Kulali; Aslihan Semiz-Oysu; Ozgul Duzgun; Yasar Bukte (Ķazaķstannyṇ Klinikalyķ Medicinasy, 2019)
Objectives: To evaluate the effectiveness of ultrasound (US) guided percutaneous abscess drainage in the treatment of adult patients with perforated appendicitis and to estimate the success rate. Material and methods: Pre-interventional computed tomography examinations of patients (n=63) who had abscess formation due to perforated appendicitis were reviewed retrospectively. A total of 15 patients [6 (40%) women and 9 (60%) men] with a mean age of 42±21 (SD) years who underwent US-guided percutaneous abscess drainage were enrolled in this study. Abscess volume, location, catheter duration and follow-up results were recorded. The treatment effectiveness of US-guided percutaneous abscess drainage was investigated. Results: A total of 15 patients were included. Abscess formations were in right lower quadrant (n=10) and deep pelvic area (n=5). The mean abscess volume was 235 mm3 (range: 20 - 1180). The mean catheter duration was 12.2 ± 7.8 days (range: 3 - 30). Five patients (5/15, 33%) were treated non-surgically with complete response. In remaining 10 patients (10/15, 67%), surgical management was required because of recurrent abscess (3/15, 20%) and progression in abscess volume (7/15, 47%). The technical success rate and the clinical success rate was 100%, and 33%, respectively. Conclusion: Because of our low clinical success rate with 33%, we recommended US-guided percutaneous abscess drainage in perforated appendicitis for some selected patients with high risk surgery.